Self-government in deeply divided societies - The kaleidoscope of efforts by the Afrikaans community to develop a comprehensive model for self-management - de Villiers, Bertus (2018)
The Afrikaans speaking community has particularly since 1994 been engaged in various activities to protect and promote the Afrikaans language. These activities remain to a large extent mainly uncoordinated and spontaneous. A central theme that runs through many of the initiatives is the desire of a substantial portion of the Afrikaans speaking community to be able to self-govern and self-manage aspects of relevance to their language and culture. Although many private initiatives have been undertaken by clubs and associations of different sorts, this article considers the constitutional mechanisms for the protection of minority and community rights under the Constitution and discusses what progress, if any, is being made by the Afrikaans community to maximise constitutional provisions and to develop a framework for self-government. The article firstly considers whether the Afrikaans community is a 'minority' for purposes of international law. The conclusion is that the community does meet the international criteria for being a 'minority'. The article secondly investigates whether there is in international law a 'right' to self-government or autonomy for minority groups. The conclusion is that there is no such a justiciable 'right', but that governments are encouraged by international law to create an environment and circumstances in which minority communities can protect and promote their unique identity. Thirdly, the article reflects on the most important mechanisms in the South African Constitution that are directed to or can be used for the protection of minority communities. The mechanisms referred to are decentralisation to provincial governments; advisory bodies to protect and promote diversity; recognition of traditional authorities; recognition of individual rights and freedoms; and the possibility to create community councils for language communities. It is concluded that these techniques are consistent with minimum international constitutional law standards. The next question is whether and to what extent the Afrikaans community has utilised the constitutional mechanisms at its disposal to protect and promote the Afrikaans language and culture. Consideration is given to the following mechanisms: (a) the autonomy of the provinces of the Western Cape and the Northern Cape where a substantial concentration of Afrikaans speakers reside; (b) the functions and responsibilities of the Pan South African Language Board and the Commission on the Promotion and Protection of Cultural, Religious and Linguistic Communities; (c) the possible establishment of an Afrikaans community council pursuant to the Constitution of the Western Cape or alternatively pursuant to the national Constitution; (d) the protection of the individual right to language choice in public education and particularly to the autonomy of school management boards; and (e) the right to free association and the plethora of Afrikaans non-governmental organisations with specific reference to Helpmekaar private college; Akademia private university; and AfriForum as a major Afrikaans community initiative. The article draws several conclusions namely: (a) there remains a general absence of agreement within the Afrikaans community in regard to a 'plan' or 'vision' for the future protection and promotion of the Afrikaans language; (b) the Afrikaans community meets the criteria to be regarded as a 'minority group' in international law; (c) there is no justiciable 'right' in international law to self-government or autonomy; (d) at a technical level the Constitution of South Africa meets minimum international criteria for the protection of individual and minority rights; (e) the autonomy of the province of the Western Cape is typical of what can be expected of indirect protection of a language group by way of territorial decentralisation. It is, however, noted that the possibility to establish a community council for the Afrikaans community pursuant to the Constitution of the Western Cape has not been activated or pursued; (f) the two constitutional commissions that are tasked to protect and promote the rights of language, cultural and religious communities have been less successful than could be expected in light of their constitutional mandate; (g) the possible establishment of a community council for the Afrikaans community remains dormant and has not attracted substantial public debate. This is a mechanism that in future may become relevant to the Afrikaans (and other) communities for purposes of their self-government; (h) the autonomy of public school management boards has attracted substantial litigation and it is likely that government regulation will further Erode and limit the autonomy of public school management boards. There are two competing interests that impact on the discretion of these boards: on the one hand the accommodation of diversity and on the other hand the provision of basic educational services to the population. The current trend is that any dispute between these two constitutional objectives are settled in favour of providing education to the widest possible group of persons; and (i) Afrikaans non-governmental organisations have been very proactive particularly since 1994. Finally, the examples of Helpmekaar and Akademia show how privatised services can be made available to the Afrikaans community, albeit at a high cost. It is likely that due to public resource constraints, a much greater contribution would have to be made in future by Afrikaans speaking families who prefer that their children be educated in Afrikaans.